INTERFERENSI POLA KALIMAT BAHASA INDONESIA TERHADAP KETERAMPILAN BERBICARA BAHASA JERMAN SISWA - Rahmayana Rahmayana; Mantasiah R; Hasmawati Hasmawati; Muddin Muddin (Makassar State University, 2018)
The purpose of this study was to find out how to use Indonesian sentence patterns on German speaking skills in class XI students of SMA 2 Bantaeng. This research is a qualitative descriptive study. The population of this study were all students of class XI SMA 2 Bantaeng. The sample in the study amounted to 32 students. The data obtained were analyzed using percentage techniques. The results of the data analysis showed that the interference with the use of Indonesian sentence patterns on students' German speaking skills was 11.4%.